Desafiando o tempo: estudo do conjunto tombado da Vila do Biribiri em Diamantina - Kamila Brant de Araújo Maurício (2015)
The research investigates the history and the current situation of the Architectural Complex of Biribiri Village, also the envirolment, the protection of the place values, especially socioeconomic and cultural values, from them, the tourism. It was one of the first manufacturing communities in Minas Gerais State and was active from 1876 to 1973, and some edifications and the textile memory are still preserved. The village had his survey homologated in state level by Instituto Estadual do Patrimônio Histórico e Artístico de Minas Gerais, IEPHA/MG in 1998.The edifications private property allowed the houses sell to happen gradualy in 2013. As a preventive measure, a plan of preservation guideline for the landscape architectual Biribiri was created by IEPHA in order to inform the new village ocupants about preservation and conservation of the complex. This work investigates not only the village history but also the reasons of its transformations functional, touristic, cultual and economic relations. It uses as methodoly : the research, historic and current data collection, analysis and diagnostics to understand the process of formal and functional transformations in the village. The study passed by the factorythe city and the park histories, using interviews with the current owners , what was necessary to the residents and the city perception and also to patrimonial and preservation body action. During the research, it was perceived that the necessary paperwork made the patrimonial organ actions and answers time-consuming. Most of the owners had begun the properties reform without respecting the IEPHA rules and guideline, presenting a new situation that made harder to the patrominial institute propose effective actions . According to IEPHA, the complex division in independente units has never been shimmered because of being, until then, a cohesive complex, of single property that is inside a countryside, what is a worry motivated by the risks of desfigurament of the complex integrity. All the interviewed owners told they had the interest in keeping the architectural patrimony. However, they started the restoration before the time, without legal patrimonial support, what it not common in property expansion in patrimonial survey area. Nevertheless, the architectual complex of Biribiri, because of the natural actions caused by the disuse along the time, was in precarious situation and Estamparia S.A. related not having conditions of keeping it. In one hand, the owners opinion, that justified the reforms as a way to revitalize the village; in the other hand, the possibility of desfigurament of the complex and lost of its values of survey. The protections by survey are not enough for the necessities and currrent problems. There is a lot to advance about patrimonial toughts and manager organ actions. We all are responsible for the cultural patromony and for its preservations for future generations.